Digital Health in Primordial and Primary Stroke Prevention: A Systematic Review. Issue 3 (3rd February 2022) - Feigin, Valery L.; Owolabi, Mayowa; Hankey, Graeme J.; Pandian, Jeyaraj; Martins, Sheila C.
Abstract : Supplemental Digital Content is available in the text. Abstract : The stroke burden continues to grow across the globe, disproportionally affecting developing countries. This burden cannot be effectively halted and reversed without effective and widely implemented primordial and primary stroke prevention measures, including those on the individual level. The unprecedented growth of smartphone and other digital technologies with digital solutions are now being used in almost every area of health, offering a unique opportunity to improve primordial and primary stroke prevention on the individual level. However, there are several issues that need to be considered to advance development and use this important digital strategy for primordial and primary stroke prevention. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines we provide a systematic review of the current knowledge, challenges, and opportunities of digital health in primordial and primary stroke prevention.